Mapping the immune and epigenetic landscape of medication-overuse headache (MOH): a systematic review - Andersen, Nanna Elman; Waliszewska-Prosół, Marta; Pellesi, Lanfranco (Frontiers in Immunology, 2026)
IntroductionMedication-overuse headache (MOH) develops when drugs intended for acute pain relief lower the threshold for headache chronification. The biological mechanisms driving this transition remain poorly understood. We aim to synthesize current evidence on immune and epigenetic alterations in MOH, identifying new targets of interest and outlining priorities for future research and precision-based interventions.MethodsWe systematically searched PubMed, Embase and Scopus from inception to May 2025 for original human or animal studies reporting immune and/or epigenetic measures in MOH. Risk of bias (RoB) was assessed with the SYRCLE tool for animal studies and JBI tools for human studies. Findings were narratively synthesized, and a domain-based strength-of-evidence (SoE) framework was applied.ResultsThirteen studies met inclusion criteria. Animal studies identified two immunological pathways involved in MOH resolution: low-dose interleukin-2-mediated expansion of regulatory T cells and inhibition of the P2X purinoceptor 7 (P2X7R)/NLRP3 inflammasome signaling. Clinical studies reported systemic low-grade inflammation in MOH patients, including elevated leukocyte counts, interleukin-6 and gut-derived inflammatory markers. Two epigenetic studies identified differential DNA methylation in genes regulating immune responses and pain transmission. Most studies were small and cross-sectional with limited adjustment. Overall SoE was low-moderate across domains.ConclusionCurrent evidence points to plausible immune and epigenetic involvement in MOH but is insufficient for causal inference or clinical guidance. Findings are hypothesis-generating and most useful for translational prioritization.